Basemembrane-supported high-ionic-conductivity solid electrolyte as well as preparation method and application thereof

The preparation method of high-ion conductivity solid-state electrolyte supported by the base film uses the synergistic effect of electric field, temperature field and pressure field to build a preferred lithium ion transmission channel, solving the problem of low ion conductivity of traditional solid electrolytes and significantly improving the performance of solid-state batteries.

CN119695290APending Publication Date: 2025-03-25TIANFU JIANGXI LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411820043.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Traditional solid electrolytes have shortcomings in ion conductivity, mechanical properties and interface compatibility, especially their low ion conductivity, which limits the application range of solid-state batteries.

Method used

The high-ion conductive solid electrolyte preparation method supported by the base film is adopted to build a solid electrolyte precursor, configure an electrolyte slurry, and apply the synergistic action of the electric field, the temperature field and the pressure field to build a preferred lithium ion transmission channel.

Benefits of technology

The ion conductivity of the solid electrolyte is significantly improved, forming a uniform and dense film, reducing the energy barrier of lithium ions, and enhancing the energy density and cycling stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695290A_ABST
    Figure CN119695290A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a basement membrane supported high-ionic-conductivity solid electrolyte, and relates to the technical field of electrochemistry, the preparation method comprises the following steps: preparing a solid electrolyte precursor: preparing the solid electrolyte precursor by taking plastic inorganic lithium salt, oxide electrolyte, a super-ionic conductor and a functional polymer additive as raw materials; preparing electrolyte slurry: sequentially adding a solvent, a plastic inorganic lithium salt, a super-ionic conductor, an oxide electrolyte and a functional polymer additive into a reaction container, and continuously stirring by using a dispersion machine in the adding process; coating solid electrolyte slurry: coating the base membrane with the solid electrolyte slurry; the solid electrolyte is cured, specifically, two curing stages are included, only the temperature is controlled during primary curing, and a pressure field and an electric field are introduced during secondary curing. The solid electrolyte prepared by the preparation method is uniform and compact, an ion transmission path with preferential guiding capability can be constructed, and the conduction performance of the solid electrolyte is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical technology, and in particular to a base film supported high ion conductivity solid electrolyte and a preparation method and application thereof. Background Art

[0002] As the core component of solid-state batteries, the performance of solid-state electrolytes is directly related to the energy density, cycle stability and safety of the battery. However, traditional solid-state electrolytes have obvious deficiencies in ion conductivity, mechanical properties and interface compatibility. Especially in terms of ion conductivity, due to the limited and discontinuous ion transmission channels in solid-state electrolytes, the ion conductivity is often low, which limits the application scope of solid-state batteries. In addition, the current solid-state electrolyte materials also have the problem of incompatibility between mechanical strength and ionic conductivity, and the solid-state electrolyte film formed is difficult to have both excellent ionic conductivity and mechanical support strength.

[0003] The solid electrolyte film with a "reinforced concrete" structure supported by a base membrane can achieve decoupling regulation between mechanical support performance and ionic conductivity performance. By regulating the material, thickness and porosity of the base membrane and optimizing the formula of the solid electrolyte material, the design and preparation of a solid electrolyte film that can meet the mechanical and electrical performance requirements of different application scenarios can be achieved. However, under the premise that mechanical properties and ionic conductivity can be decoupled and regulated, there are still great challenges in how to improve the ionic conductivity of the solid electrolyte and prepare a solid electrolyte that uniformly and densely fills the gaps in the base membrane.

[0004] In terms of improving the ionic conductivity of solid electrolytes, two-dimensional and three-dimensional porous nanomaterials have shown great potential due to their unique nanostructures and physicochemical properties. Two-dimensional nanomaterials have single-layer or multi-layer structures and rich surface interfaces, which can provide favorable conditions for the adsorption and transport of ions. Three-dimensional porous nanomaterials, with their highly developed pore structures and easily regulated surface and interface properties, are conducive to the precise control and efficient transport of ions. When the size of these materials is reduced to the nanoscale or has nanoscale pores, the significantly enhanced nanoconfinement effect can more effectively restrict and guide ion transport, providing a new way to construct efficient ion transport channels to improve the ionic conductivity of solid electrolytes. However, how to effectively introduce nanoconfinement materials into solid electrolytes in the form of nanoscale or nanopores, and how to optimize the ion transport path to improve ionic conductivity, are both urgent problems to be solved. Summary of the invention

[0005] Based on the problem of weak ion conductivity of current solid electrolytes, the purpose of the present invention is to provide a base membrane supported high ion conductivity solid electrolyte and its preparation method and application. The solid electrolyte prepared by this preparation method is uniform and dense, and can construct an ion transmission path with preferential guiding capability, thereby significantly improving the conductivity of the solid electrolyte.

[0006] The present invention is achieved through the following technical solutions:

[0007] In a first aspect, the present application provides a method for preparing a substrate-supported high ionic conductivity solid electrolyte, comprising the following steps:

[0008] Preparation of solid electrolyte precursor: Prepare solid electrolyte precursor using plastic inorganic lithium salt, oxide electrolyte, superionic conductor and functional polymer additive as raw materials;

[0009] Prepare electrolyte slurry: add solvent, plastic inorganic lithium salt, superionic conductor, oxide electrolyte, and functional polymer additive into the reaction container in sequence, and use a disperser to continuously stir during the addition process;

[0010] Applying solid electrolyte slurry: applying the solid electrolyte slurry on the base film;

[0011] Solidified solid electrolyte: includes two solidification stages, in which only the temperature is controlled during the initial solidification, and the temperature field, pressure field and electric field are introduced during the secondary solidification.

[0012] Among them, the uniform configuration of the precursor depends on the reasonable setting of the feeding order and the reasonable use of particle breakage and stirring equipment. Specifically, a low-viscosity liquid is added first, and then solid particles and other additives are gradually added. The high-speed rotating dispersion disk of the high-speed disperser is used to break the particle agglomerates, and the cavitation effect of the ultrasonic stirring container is used to evenly disperse the particles. First, the stirring speed of the high-speed disperser is controlled to 1000-5000rpm, and the stirring time is 1-5 hours; then, an ultrasonic agitator is used for ultrasonic stirring for 1-5 hours (power 1000-3000W); finally, the stirring speed of the high-speed disperser is controlled at 1000-5000rpm, and the stirring time is 1-5 hours. According to actual needs, the stirring process is repeated 1-3 times, and multiple stirring can be performed again after each standing to improve the uniformity of the slurry.

[0013] During the coating process, the tension roller under the coating head provides stable film support, and reduces wrinkles and deformation during the coating process by adjusting the film tension, ensuring that the solid electrolyte slurry maintains stable fluidity and uniformity during the coating process. The vacuum negative pressure system is used to effectively adsorb and guide the electrolyte slurry into the pores of the base film, achieving deep penetration and efficient filling.

[0014] The present invention utilizes the synergistic effect of temperature field, pressure field and electric field to realize the in-situ curing process of solid electrolyte slurry. Under the action of multi-field coupling, the solvent guides the uniform dispersion of the precursor and the full infiltration of the interface. The high temperature triggers the cross-linking and curing of the polymer molecules. The pressure difference discharges the redundant materials and solvent molecules. The electric field induces the orientation arrangement of the ion conductor additives to form a preferentially guided lithium ion transmission channel and enhance the ion migration ability. Specifically, under the action of negative pressure, precise temperature control is used to achieve the chemical conversion and preliminary curing of the electrolyte precursor in the pores of the basement membrane, and then the electric field-assisted in-situ curing technology is used to form a continuous, dense, high-speed ion transmission network in the pores of the basement membrane. The formed solid electrolyte has a "reinforced concrete" structure.

[0015] In a specific embodiment, the plastic inorganic lithium salt includes any one or more combinations of LiCl, LiBr, Li2S, and LiNO3.

[0016] In a specific embodiment, the oxide electrolyte includes any one of ZrO2 and La2O3 or a combination of two.

[0017] In a specific embodiment, the superionic conductor includes any one of two-dimensional nanomaterials and three-dimensional porous nanomaterials, or a combination of both.

[0018] In a specific embodiment, the two-dimensional nanomaterial includes any one of graphene, graphene derivatives, boron nitride, transition metal sulfide, carbon nitride, and two-dimensional transition metal carbide.

[0019] In a specific embodiment, the three-dimensional porous nanomaterial includes an organic metal framework, a covalent organic framework, a hydrogen bond organic framework and derivatives thereof.

[0020] In a specific embodiment, the functional polymer additive includes any one or more combinations of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-chlorotrifluoroethylene copolymer, polyethylene oxide, and polytetrafluoroethylene.

[0021] In a specific embodiment, the solvent includes any one or more combinations of N,N-dimethylformamide, N-methylpyrrolidone, and tetrahydrofuran.

[0022] In a specific embodiment, during the primary curing process, the curing temperature is 40-85°C; during the secondary curing process, the curing temperature is 40-85°C, the pressure is 0.01-1MPa, the electric field voltage is 50-200V, and the angle between the electric field direction and the horizontal direction is 30-90°.

[0023] In a specific embodiment, the concentration ratio of the plastic inorganic lithium salt, the oxide electrolyte, the superionic conductor, and the functional polymer additive is (17.0-60.8): (20-120): (2.4-26): (80-130).

[0024] In a specific embodiment, when the solid electrolyte slurry is coated on the base film, the coating speed is 50 to 2000 mm / s, and the pressure is controlled at -1 to -100 kPa.

[0025] In a second aspect, the present application provides a base film supported high ionic conductivity solid electrolyte, which is prepared using the above-mentioned preparation method.

[0026] In a third aspect, the present application provides a secondary battery, comprising a solid electrolyte prepared by the above method. The secondary battery comprises a button-type secondary battery.

[0027] In a specific embodiment, the secondary battery is prepared by cutting a solid electrolyte film into discs, clamping the discs between two pieces of stainless steel to form a "sandwich" structure, placing the discs in a battery casing, injecting a liquid electrolyte, and encapsulating the discs to obtain a secondary battery.

[0028] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0029] (1) The preparation method of the solid electrolyte in the present invention can construct in situ a uniform and dense solid electrolyte film with a preferential lithium ion transmission channel through the synergistic effect of the electric field, temperature field, and pressure field during the solidification process, thereby significantly reducing the lithium ion migration energy barrier and improving the ion conductivity; the solid electrolyte is evenly filled in the gaps of the base film to form a uniform and dense film.

[0030] (2) The formula of the solid electrolyte precursor used in the present invention can improve the ionic conductivity, thermal stability, low temperature adaptability, electrochemical stability and antioxidant capacity of the solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0032] Figure 1 It is a curing process diagram of a method for preparing a base film-supported high ion conductivity solid electrolyte in the present invention;

[0033] Figure 2This is a schematic diagram of the microstructure of the solid electrolyte with ionic superconducting additives arranged in a directional manner in Example 1 of the present invention;

[0034] Figure 3 A schematic diagram of the microstructure of the solid electrolyte in which the ionic superconducting additives are randomly arranged in Comparative Example 1;

[0035] Figure 4 Schematic diagram of the microstructure of the solid electrolyte in Comparative Example 4 without adding ionic superconducting additives. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0037] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to one of ordinary skill in the art that these specific details need not be employed to practice the present invention. In other embodiments, in order to avoid confusing the present invention, well-known materials or methods are not specifically described.

[0038] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment," "an embodiment," "an example," or "an example" that appear in various places throughout the specification do not necessarily all refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any appropriate combination and / or sub-combination. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items. In addition, those skilled in the art will be able to combine and combine different embodiments or examples described in this specification and features of different embodiments or examples, without contradicting each other.

[0039] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0040] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0041] Example 1

[0042] This embodiment provides a method for preparing a base film-supported high ionic conductivity solid electrolyte, which is carried out according to the following steps:

[0043] S1. Prepare solid electrolyte precursor

[0044] Solid electrolyte precursors are prepared using plastic inorganic lithium salts, oxide electrolytes, superionic conductors, and functional polymer additives as raw materials;

[0045] Among them, the plastic inorganic lithium salts are LiCl and LiNO3, with a total concentration of 25.6g / L and a concentration ratio of 1:1. The oxide electrolytes are ZrO2 and La2O3, with a concentration of 30g / L and a mass ratio of 1:1. The functional polymer additives are polyvinylidene fluoride and polyethylene oxide, with a concentration of 110g / L and a mass ratio of 1:1. The superionic conductor is a mixture of graphene oxide and reduced graphene, with a total mass concentration of 15g / L and a mass ratio of 1:1. The solvent is N,N-dimethylformamide and N-methylpyrrolidone, with a volume ratio of 1:3.

[0046] S2. Prepare electrolyte slurry

[0047] A mixture of N,N-dimethylformamide and N-methylpyrrolidone, a mixture of LiCl and LiNO3, a mixture of graphene oxide and reduced graphene, a mixture of ZrO2 and La2O3, and a mixture of polyvinylidene fluoride and polyethylene oxide were added to the reaction container in sequence. During the addition process, the high-speed disperser continued to work and the stirring speed was controlled at 2000 rpm. After the addition was completed, stirring was continued for 1 hour, and then the ultrasonic stirrer was used for 2 hours at 2000 W. Then, the high-speed disperser was used to stir at 2000 rpm for 2 hours. After standing for 4 hours, the above stirring process was repeated once.

[0048] S3. Coating solid electrolyte

[0049] A PE base film was selected with a thickness of 16 μm, a porosity of 50%, a coating speed of 200 mm / s, and a negative pressure of -10 kPa.

[0050] S4, Solidified solid electrolyte

[0051] Initial curing: curing temperature is 60°C and curing time is 1 hour.

[0052] Secondary curing: curing temperature is 60℃, pressure is 0.5MPa, electric field voltage is 100V, electric field angle is 90°, and curing time is 2 hours. Figure 1 shown.

[0053] Example 2

[0054] This embodiment provides a method for preparing a base film supported high ionic conductivity solid electrolyte. The difference from Example 1 is that a 60° electric field is applied in the curing step of this embodiment. Other technical features are the same as those of Example 1.

[0055] Follow these steps:

[0056] S1. Prepare solid electrolyte precursor

[0057] Solid electrolyte precursors are prepared using plastic inorganic lithium salts, oxide electrolytes, superionic conductors, and functional polymer additives as raw materials;

[0058] Among them, the plastic inorganic lithium salts are LiCl and LiNO3, with a total concentration of 25.6g / L and a concentration ratio of 1:1. The oxide electrolytes are ZrO2 and La2O3, with a concentration of 30g / L and a mass ratio of 1:1. The functional polymer additives are polyvinylidene fluoride and polyethylene oxide, with a concentration of 110g / L and a mass ratio of 1:1. The superionic conductor is a mixture of graphene oxide and reduced graphene, with a total mass concentration of 15g / L and a mass ratio of 1:1. The solvent is N,N-dimethylformamide and N-methylpyrrolidone, with a volume ratio of 1:3.

[0059] S2. Prepare electrolyte slurry

[0060] A mixture of N,N-dimethylformamide and N-methylpyrrolidone, a mixture of LiCl and LiNO3, a mixture of graphene oxide and reduced graphene, a mixture of ZrO2 and La2O3, and a mixture of polyvinylidene fluoride and polyethylene oxide were added to the reaction container in sequence. During the addition process, the high-speed disperser continued to work and the stirring speed was controlled at 2000 rpm. After the addition was completed, stirring was continued for 1 hour, and then the ultrasonic stirrer was used for 2 hours at 2000 W. Then, the high-speed disperser was used to stir at 2000 rpm for 2 hours. After standing for 4 hours, the above stirring process was repeated once.

[0061] S3. Coating solid electrolyte

[0062] A PE base film was selected with a thickness of 16 μm, a porosity of 50%, a coating speed of 200 mm / s, and a negative pressure of -10 kPa.

[0063] S4, Solidified solid electrolyte

[0064] Initial curing: curing temperature is 60°C and curing time is 1 hour.

[0065] Secondary curing: curing temperature is 60℃, pressure is 0.5MPa, electric field voltage is 100V, electric field angle is 60°, and curing time is 2 hours. Figure 1 shown.

[0066] Example 3

[0067] This embodiment provides a method for preparing a base film supported high ionic conductivity solid electrolyte. The difference from Example 1 is that a 45° electric field is applied in the curing step of this embodiment. Other technical features are the same as those of Example 1.

[0068] Follow these steps:

[0069] S1. Prepare solid electrolyte precursor

[0070] Solid electrolyte precursors are prepared using plastic inorganic lithium salts, oxide electrolytes, superionic conductors, and functional polymer additives as raw materials;

[0071] Among them, the plastic inorganic lithium salts are LiCl and LiNO3, with a total concentration of 25.6g / L and a concentration ratio of 1:1. The oxide electrolytes are ZrO2 and La2O3, with a concentration of 30g / L and a mass ratio of 1:1. The functional polymer additives are polyvinylidene fluoride and polyethylene oxide, with a concentration of 110g / L and a mass ratio of 1:1. The superionic conductor is a mixture of graphene oxide and reduced graphene, with a total mass concentration of 15g / L and a mass ratio of 1:1. The solvent is N,N-dimethylformamide and N-methylpyrrolidone, with a volume ratio of 1:3.

[0072] S2. Prepare electrolyte slurry

[0073] A mixture of N,N-dimethylformamide and N-methylpyrrolidone, a mixture of LiCl and LiNO3, a mixture of graphene oxide and reduced graphene, a mixture of ZrO2 and La2O3, and a mixture of polyvinylidene fluoride and polyethylene oxide were added to the reaction container in sequence. During the addition process, the high-speed disperser continued to work and the stirring speed was controlled at 2000 rpm. After the addition was completed, stirring was continued for 1 hour, and then the ultrasonic stirrer was used for 2 hours at 2000 W. Then, the high-speed disperser was used to stir at 2000 rpm for 2 hours. After standing for 4 hours, the above stirring process was repeated once.

[0074] S3. Coating solid electrolyte

[0075] A PE base film was selected with a thickness of 16 μm, a porosity of 50%, a coating speed of 200 mm / s, and a negative pressure of -10 kPa.

[0076] S4, Solidified solid electrolyte

[0077] Initial curing: curing temperature is 60°C and curing time is 1 hour.

[0078] Secondary curing: curing temperature is 60℃, pressure is 0.5MPa, electric field voltage is 100V, electric field angle is 45°, and curing time is 2 hours. Figure 1 shown.

[0079] Example 4

[0080] This embodiment provides a method for preparing a base film supported high ionic conductivity solid electrolyte. The difference from Example 1 is that a 30° electric field is applied in the curing step of this embodiment. Other technical features are the same as those of Example 1.

[0081] Follow these steps:

[0082] S1. Prepare solid electrolyte precursor

[0083] Solid electrolyte precursors are prepared using plastic inorganic lithium salts, oxide electrolytes, superionic conductors, and functional polymer additives as raw materials;

[0084] Among them, the plastic inorganic lithium salts are LiCl and LiNO3, with a total concentration of 25.6g / L and a concentration ratio of 1:1. The oxide electrolytes are ZrO2 and La2O3, with a concentration of 30g / L and a mass ratio of 1:1. The functional polymer additives are polyvinylidene fluoride and polyethylene oxide, with a concentration of 110g / L and a mass ratio of 1:1. The superionic conductor is a mixture of graphene oxide and reduced graphene, with a total mass concentration of 15g / L and a mass ratio of 1:1. The solvent is N,N-dimethylformamide and N-methylpyrrolidone, with a volume ratio of 1:3.

[0085] S2. Prepare electrolyte slurry

[0086] A mixture of N,N-dimethylformamide and N-methylpyrrolidone, a mixture of LiCl and LiNO3, a mixture of graphene oxide and reduced graphene, a mixture of ZrO2 and La2O3, and a mixture of polyvinylidene fluoride and polyethylene oxide were added to the reaction container in sequence. During the addition process, the high-speed disperser continued to work and the stirring speed was controlled at 2000 rpm. After the addition was completed, stirring was continued for 1 hour, and then the ultrasonic stirrer was used for 2 hours at 2000 W. Then, the high-speed disperser was used to stir at 2000 rpm for 2 hours. After standing for 4 hours, the above stirring process was repeated once.

[0087] S3. Coating solid electrolyte

[0088] A PE base film was selected with a thickness of 16 μm, a porosity of 50%, a coating speed of 200 mm / s, and a negative pressure of -10 kPa.

[0089] S4, Solidified solid electrolyte

[0090] Initial curing: curing temperature is 60°C and curing time is 1 hour.

[0091] Secondary curing: curing temperature is 60℃, pressure is 0.5MPa, electric field voltage is 100V, electric field angle is 30°, and curing time is 2 hours. Figure 1 shown.

[0092] Example 5

[0093] This embodiment provides a method for preparing a base film supported high ionic conductivity solid electrolyte. The difference from Example 1 is that the voltage applied in the curing step of this embodiment is 50V, and the other technical features are the same as those of Example 1.

[0094] Follow these steps:

[0095] S1. Prepare solid electrolyte precursor

[0096] Solid electrolyte precursors are prepared using plastic inorganic lithium salts, oxide electrolytes, superionic conductors, and functional polymer additives as raw materials;

[0097] Among them, the plastic inorganic lithium salts are LiCl and LiNO3, with a total concentration of 25.6g / L and a concentration ratio of 1:1. The oxide electrolytes are ZrO2 and La2O3, with a concentration of 30g / L and a mass ratio of 1:1. The functional polymer additives are polyvinylidene fluoride and polyethylene oxide, with a concentration of 110g / L and a mass ratio of 1:1. The superionic conductor is a mixture of graphene oxide and reduced graphene, with a total mass concentration of 15g / L and a mass ratio of 1:1. The solvent is N,N-dimethylformamide and N-methylpyrrolidone, with a volume ratio of 1:3.

[0098] S2. Prepare electrolyte slurry

[0099] A mixture of N,N-dimethylformamide and N-methylpyrrolidone, a mixture of LiCl and LiNO3, a mixture of graphene oxide and reduced graphene, a mixture of ZrO2 and La2O3, and a mixture of polyvinylidene fluoride and polyethylene oxide were added to the reaction container in sequence. During the addition process, the high-speed disperser continued to work and the stirring speed was controlled at 2000 rpm. After the addition was completed, stirring was continued for 1 hour, and then the ultrasonic stirrer was used for 2 hours at 2000 W. Then, the high-speed disperser was used to stir at 2000 rpm for 2 hours. After standing for 4 hours, the above stirring process was repeated once.

[0100] S3. Coating solid electrolyte

[0101] A PE base film was selected with a thickness of 16 μm, a porosity of 50%, a coating speed of 200 mm / s, and a negative pressure of -10 kPa.

[0102] S4, Solidified solid electrolyte

[0103] Initial curing: curing temperature is 60°C and curing time is 1 hour.

[0104] Secondary curing: curing temperature is 60℃, pressure is 0.5MPa, electric field voltage is 50V, electric field angle is 90°, curing time is 2 hours. Figure 1 shown.

[0105] Example 6

[0106] This embodiment provides a method for preparing a base film supported high ionic conductivity solid electrolyte. The difference from Example 1 is that the voltage applied in the curing step of this embodiment is 200V, and the other technical features are the same as those of Example 1.

[0107] Follow these steps:

[0108] S1. Prepare solid electrolyte precursor

[0109] Solid electrolyte precursors are prepared using plastic inorganic lithium salts, oxide electrolytes, superionic conductors, and functional polymer additives as raw materials;

[0110] Among them, the plastic inorganic lithium salts are LiCl and LiNO3, with a total concentration of 25.6g / L and a concentration ratio of 1:1. The oxide electrolytes are ZrO2 and La2O3, with a concentration of 30g / L and a mass ratio of 1:1. The functional polymer additives are polyvinylidene fluoride and polyethylene oxide, with a concentration of 110g / L and a mass ratio of 1:1. The superionic conductor is a mixture of graphene oxide and reduced graphene, with a total mass concentration of 15g / L and a mass ratio of 1:1. The solvent is N,N-dimethylformamide and N-methylpyrrolidone, with a volume ratio of 1:3.

[0111] S2. Prepare electrolyte slurry

[0112] A mixture of N,N-dimethylformamide and N-methylpyrrolidone, a mixture of LiCl and LiNO3, a mixture of graphene oxide and reduced graphene, a mixture of ZrO2 and La2O3, and a mixture of polyvinylidene fluoride and polyethylene oxide were added to the reaction container in sequence. During the addition process, the high-speed disperser continued to work and the stirring speed was controlled at 2000 rpm. After the addition was completed, stirring was continued for 1 hour, and then the ultrasonic stirrer was used for 2 hours at 2000 W. Then, the high-speed disperser was used to stir at 2000 rpm for 2 hours. After standing for 4 hours, the above stirring process was repeated once.

[0113] S3. Coating solid electrolyte

[0114] A PE base film was selected with a thickness of 16 μm, a porosity of 50%, a coating speed of 200 mm / s, and a negative pressure of -10 kPa.

[0115] S4, Solidified solid electrolyte

[0116] Initial curing: curing temperature is 60°C and curing time is 1 hour.

[0117] Secondary curing: curing temperature is 60℃, pressure is 0.5MPa, electric field voltage is 200V, electric field angle is 90°, and curing time is 2 hours. Figure 1 shown.

[0118] Example 7

[0119] This embodiment provides a method for preparing a base film supported high ionic conductivity solid electrolyte. The difference from Example 1 is that the pressure applied in the curing step of this embodiment is 0.01 MPa, and the other technical features are the same as those of Example 1.

[0120] Follow these steps:

[0121] S1. Prepare solid electrolyte precursor

[0122] Solid electrolyte precursors are prepared using plastic inorganic lithium salts, oxide electrolytes, superionic conductors, and functional polymer additives as raw materials;

[0123] Among them, the plastic inorganic lithium salts are LiCl and LiNO3, with a total concentration of 25.6g / L and a concentration ratio of 1:1. The oxide electrolytes are ZrO2 and La2O3, with a concentration of 30g / L and a mass ratio of 1:1. The functional polymer additives are polyvinylidene fluoride and polyethylene oxide, with a concentration of 110g / L and a mass ratio of 1:1. The superionic conductor is a mixture of graphene oxide and reduced graphene, with a total mass concentration of 15g / L and a mass ratio of 1:1. The solvent is N,N-dimethylformamide and N-methylpyrrolidone, with a volume ratio of 1:3.

[0124] S2. Prepare electrolyte slurry

[0125] A mixture of N,N-dimethylformamide and N-methylpyrrolidone, a mixture of LiCl and LiNO3, a mixture of graphene oxide and reduced graphene, a mixture of ZrO2 and La2O3, and a mixture of polyvinylidene fluoride and polyethylene oxide were added to the reaction container in sequence. During the addition process, the high-speed disperser continued to work and the stirring speed was controlled at 2000 rpm. After the addition was completed, stirring was continued for 1 hour, and then the ultrasonic stirrer was used for 2 hours at 2000 W. Then, the high-speed disperser was used to stir at 2000 rpm for 2 hours. After standing for 4 hours, the above stirring process was repeated once.

[0126] S3. Coating solid electrolyte

[0127] A PE base film was selected with a thickness of 16 μm, a porosity of 50%, a coating speed of 200 mm / s, and a negative pressure of -10 kPa.

[0128] S4, Solidified solid electrolyte

[0129] Initial curing: curing temperature is 60°C and curing time is 1 hour.

[0130] Secondary curing: curing temperature is 60℃, pressure is 0.01MPa, electric field voltage is 100V, electric field angle is 90°, and curing time is 2 hours. Figure 1 shown.

[0131] Example 8

[0132] This embodiment provides a method for preparing a base film supported high ionic conductivity solid electrolyte. The difference from Example 1 is that the pressure applied in the curing step of this embodiment is 0.8 MPa, and the other technical features are the same as those of Example 1.

[0133] Follow these steps:

[0134] S1. Prepare solid electrolyte precursor

[0135] Solid electrolyte precursors are prepared using plastic inorganic lithium salts, oxide electrolytes, superionic conductors, and functional polymer additives as raw materials;

[0136] Among them, the plastic inorganic lithium salts are LiCl and LiNO3, with a total concentration of 25.6g / L and a concentration ratio of 1:1. The oxide electrolytes are ZrO2 and La2O3, with a concentration of 30g / L and a mass ratio of 1:1. The functional polymer additives are polyvinylidene fluoride and polyethylene oxide, with a concentration of 110g / L and a mass ratio of 1:1. The superionic conductor is a mixture of graphene oxide and reduced graphene, with a total mass concentration of 15g / L and a mass ratio of 1:1. The solvent is N,N-dimethylformamide and N-methylpyrrolidone, with a volume ratio of 1:3.

[0137] S2. Prepare electrolyte slurry

[0138] A mixture of N,N-dimethylformamide and N-methylpyrrolidone, a mixture of LiCl and LiNO3, a mixture of graphene oxide and reduced graphene, a mixture of ZrO2 and La2O3, and a mixture of polyvinylidene fluoride and polyethylene oxide were added to the reaction container in sequence. During the addition process, the high-speed disperser continued to work and the stirring speed was controlled at 2000 rpm. After the addition was completed, stirring was continued for 1 hour, and then the ultrasonic stirrer was used for 2 hours at 2000 W. Then, the high-speed disperser was used to stir at 2000 rpm for 2 hours. After standing for 4 hours, the above stirring process was repeated once.

[0139] S3. Coating solid electrolyte

[0140] A PE base film was selected with a thickness of 16 μm, a porosity of 50%, a coating speed of 200 mm / s, and a negative pressure of -10 kPa.

[0141] S4, Solidified solid electrolyte

[0142] Initial curing: curing temperature is 60°C and curing time is 1 hour.

[0143] Secondary curing: curing temperature is 60℃, pressure is 0.01MPa, electric field voltage is 100V, electric field angle is 90°, and curing time is 2 hours. Figure 1 shown.

[0144] Example 9

[0145] This embodiment provides a method for preparing a base film supported high ionic conductivity solid electrolyte. The difference from Example 1 is that the temperature applied in the curing step of this embodiment is 40° C., and the other technical features are the same as those of Example 1.

[0146] Follow these steps:

[0147] S1. Prepare solid electrolyte precursor

[0148] Solid electrolyte precursors are prepared using plastic inorganic lithium salts, oxide electrolytes, superionic conductors, and functional polymer additives as raw materials;

[0149] Among them, the plastic inorganic lithium salts are LiCl and LiNO3, with a total concentration of 25.6g / L and a concentration ratio of 1:1. The oxide electrolytes are ZrO2 and La2O3, with a concentration of 30g / L and a mass ratio of 1:1. The functional polymer additives are polyvinylidene fluoride and polyethylene oxide, with a concentration of 110g / L and a mass ratio of 1:1. The superionic conductor is a mixture of graphene oxide and reduced graphene, with a total mass concentration of 15g / L and a mass ratio of 1:1. The solvent is N,N-dimethylformamide and N-methylpyrrolidone, with a volume ratio of 1:3.

[0150] S2. Prepare electrolyte slurry

[0151] A mixture of N,N-dimethylformamide and N-methylpyrrolidone, a mixture of LiCl and LiNO3, a mixture of graphene oxide and reduced graphene, a mixture of ZrO2 and La2O3, and a mixture of polyvinylidene fluoride and polyethylene oxide were added to the reaction container in sequence. During the addition process, the high-speed disperser continued to work and the stirring speed was controlled at 2000 rpm. After the addition was completed, stirring was continued for 1 hour, and then the ultrasonic stirrer was used for 2 hours at 2000 W. Then, the high-speed disperser was used to stir at 2000 rpm for 2 hours. After standing for 4 hours, the above stirring process was repeated once.

[0152] S3. Coating solid electrolyte

[0153] A PE base film was selected with a thickness of 16 μm, a porosity of 50%, a coating speed of 200 mm / s, and a negative pressure of -10 kPa.

[0154] S4, Solidified solid electrolyte

[0155] Initial curing: curing temperature is 40°C and curing time is 1 hour.

[0156] Secondary curing: curing temperature is 40℃, pressure is 0.5MPa, electric field voltage is 100V, electric field angle is 90°, and curing time is 2 hours. Figure 1 shown.

[0157] Example 10

[0158] This embodiment provides a method for preparing a base film supported high ionic conductivity solid electrolyte. The difference from Example 1 is that the temperature applied in the curing step of this embodiment is 80°C, and the other technical features are the same as those of Example 1.

[0159] Follow these steps:

[0160] S1. Prepare solid electrolyte precursor

[0161] Solid electrolyte precursors are prepared using plastic inorganic lithium salts, oxide electrolytes, superionic conductors, and functional polymer additives as raw materials;

[0162] Among them, the plastic inorganic lithium salts are LiCl and LiNO3, with a total concentration of 25.6g / L and a concentration ratio of 1:1. The oxide electrolytes are ZrO2 and La2O3, with a concentration of 30g / L and a mass ratio of 1:1. The functional polymer additives are polyvinylidene fluoride and polyethylene oxide, with a concentration of 110g / L and a mass ratio of 1:1. The superionic conductor is a mixture of graphene oxide and reduced graphene, with a total mass concentration of 15g / L and a mass ratio of 1:1. The solvent is N,N-dimethylformamide and N-methylpyrrolidone, with a volume ratio of 1:3.

[0163] S2. Prepare electrolyte slurry

[0164] A mixture of N,N-dimethylformamide and N-methylpyrrolidone, a mixture of LiCl and LiNO3, a mixture of graphene oxide and reduced graphene, a mixture of ZrO2 and La2O3, and a mixture of polyvinylidene fluoride and polyethylene oxide were added to the reaction container in sequence. During the addition process, the high-speed disperser continued to work and the stirring speed was controlled at 2000 rpm. After the addition was completed, stirring was continued for 1 hour, and then the ultrasonic stirrer was used for 2 hours at 2000 W. Then, the high-speed disperser was used to stir at 2000 rpm for 2 hours. After standing for 4 hours, the above stirring process was repeated once.

[0165] S3. Coating solid electrolyte

[0166] A PE base film was selected with a thickness of 16 μm, a porosity of 50%, a coating speed of 200 mm / s, and a negative pressure of -10 kPa.

[0167] S4, Solidified solid electrolyte

[0168] Initial curing: curing temperature is 80°C and curing time is 1 hour.

[0169] Secondary curing: curing temperature is 80℃, pressure is 0.5MPa, electric field voltage is 100V, electric field angle is 90°, and curing time is 2 hours. Figure 1 shown.

[0170] Comparative Example 1

[0171] The difference between this comparative example and Example 1 is that no electric field is applied.

[0172] Follow these steps:

[0173] S1. Prepare solid electrolyte precursor

[0174] Solid electrolyte precursors are prepared using plastic inorganic lithium salts, oxide electrolytes, superionic conductors, and functional polymer additives as raw materials;

[0175] Among them, the plastic inorganic lithium salts are LiCl and LiNO3, with a total concentration of 25.6g / L and a concentration ratio of 1:1. The oxide electrolytes are ZrO2 and La2O3, with a concentration of 30g / L and a mass ratio of 1:1. The functional polymer additives are polyvinylidene fluoride and polyethylene oxide, with a concentration of 110g / L and a mass ratio of 1:1. The superionic conductor is a mixture of graphene oxide and reduced graphene, with a total mass concentration of 15g / L and a mass ratio of 1:1. The solvent is N,N-dimethylformamide and N-methylpyrrolidone, with a volume ratio of 1:3.

[0176] S2. Prepare electrolyte slurry

[0177] A mixture of N,N-dimethylformamide and N-methylpyrrolidone, a mixture of LiCl and LiNO3, a mixture of graphene oxide and reduced graphene, a mixture of ZrO2 and La2O3, and a mixture of polyvinylidene fluoride and polyethylene oxide were added to the reaction container in sequence. During the addition process, the high-speed disperser continued to work and the stirring speed was controlled at 2000 rpm. After the addition was completed, stirring was continued for 1 hour, and then the ultrasonic stirrer was used for 2 hours at 2000 W. Then, the high-speed disperser was used to stir at 2000 rpm for 2 hours. After standing for 4 hours, the above stirring process was repeated once.

[0178] S3. Coating solid electrolyte

[0179] A PE base film was selected with a thickness of 16 μm, a porosity of 50%, a coating speed of 200 mm / s, and a negative pressure of -10 kPa.

[0180] S4, Solidified solid electrolyte

[0181] Initial curing: curing temperature is 60°C and curing time is 1 hour.

[0182] Secondary curing: curing temperature is 60°C, pressure is 0.5MPa, and curing time is 2 hours.

[0183] Comparative Example 2

[0184] The difference between this comparative example and Example 1 is that no pressure is applied.

[0185] Follow these steps:

[0186] S1. Prepare solid electrolyte precursor

[0187] Solid electrolyte precursors are prepared using plastic inorganic lithium salts, oxide electrolytes, superionic conductors, and functional polymer additives as raw materials;

[0188] Among them, the plastic inorganic lithium salts are LiCl and LiNO3, with a total concentration of 25.6g / L and a concentration ratio of 1:1. The oxide electrolytes are ZrO2 and La2O3, with a concentration of 30g / L and a mass ratio of 1:1. The functional polymer additives are polyvinylidene fluoride and polyethylene oxide, with a concentration of 110g / L and a mass ratio of 1:1. The superionic conductor is a mixture of graphene oxide and reduced graphene, with a total mass concentration of 15g / L and a mass ratio of 1:1. The solvent is N,N-dimethylformamide and N-methylpyrrolidone, with a volume ratio of 1:3.

[0189] S2. Prepare electrolyte slurry

[0190] A mixture of N,N-dimethylformamide and N-methylpyrrolidone, a mixture of LiCl and LiNO3, a mixture of graphene oxide and reduced graphene, a mixture of ZrO2 and La2O3, and a mixture of polyvinylidene fluoride and polyethylene oxide were added to the reaction container in sequence. During the addition process, the high-speed disperser continued to work and the stirring speed was controlled at 2000 rpm. After the addition was completed, stirring was continued for 1 hour, and then the ultrasonic stirrer was used for 2 hours at 2000 W. Then, the high-speed disperser was used to stir at 2000 rpm for 2 hours. After standing for 4 hours, the above stirring process was repeated once.

[0191] S3. Coating solid electrolyte

[0192] A PE base film was selected with a thickness of 16 μm, a porosity of 50%, a coating speed of 200 mm / s, and a negative pressure of -10 kPa.

[0193] S4, Solidified solid electrolyte

[0194] Initial curing: curing temperature is 60°C and curing time is 1 hour.

[0195] Secondary curing: curing temperature is 60°C, electric field voltage is 100V, electric field angle is 90°, and curing time is 2 hours.

[0196] Comparative Example 3

[0197] The difference between this comparative example and Example 1 is that no temperature is applied.

[0198] Follow these steps:

[0199] S1. Prepare solid electrolyte precursor

[0200] Solid electrolyte precursors are prepared using plastic inorganic lithium salts, oxide electrolytes, superionic conductors, and functional polymer additives as raw materials;

[0201] Among them, the plastic inorganic lithium salts are LiCl and LiNO3, with a total concentration of 25.6g / L and a concentration ratio of 1:1. The oxide electrolytes are ZrO2 and La2O3, with a concentration of 30g / L and a mass ratio of 1:1. The functional polymer additives are polyvinylidene fluoride and polyethylene oxide, with a concentration of 110g / L and a mass ratio of 1:1. The superionic conductor is a mixture of graphene oxide and reduced graphene, with a total mass concentration of 15g / L and a mass ratio of 1:1. The solvent is N,N-dimethylformamide and N-methylpyrrolidone, with a volume ratio of 1:3.

[0202] S2. Prepare electrolyte slurry

[0203] A mixture of N,N-dimethylformamide and N-methylpyrrolidone, a mixture of LiCl and LiNO3, a mixture of graphene oxide and reduced graphene, a mixture of ZrO2 and La2O3, and a mixture of polyvinylidene fluoride and polyethylene oxide were added to the reaction container in sequence. During the addition process, the high-speed disperser continued to work and the stirring speed was controlled at 2000 rpm. After the addition was completed, stirring was continued for 1 hour, and then the ultrasonic stirrer was used for 2 hours at 2000 W. Then, the high-speed disperser was used to stir at 2000 rpm for 2 hours. After standing for 4 hours, the above stirring process was repeated once.

[0204] S3. Coating solid electrolyte

[0205] A PE base film was selected with a thickness of 16 μm, a porosity of 50%, a coating speed of 200 mm / s, and a negative pressure of -10 kPa.

[0206] S4, Solidified solid electrolyte

[0207] Initial curing: curing temperature is 60°C and curing time is 1 hour.

[0208] Secondary curing: pressure is 0.5MPa, electric field voltage is 100V, electric field angle is 90°, and curing time is 2 hours.

[0209] Comparative Example 4

[0210] The difference between this comparative example and Example 1 is that no superionic conductor is added to the solid electrolyte precursor of this comparative example.

[0211] Follow these steps:

[0212] S1. Prepare solid electrolyte precursor

[0213] The solid electrolyte precursor is prepared using plastic inorganic lithium salt, oxide electrolyte and functional polymer additive as raw materials;

[0214] Among them, the plastic inorganic lithium salts are LiCl and LiNO3, with a total concentration of 25.6g / L and a concentration ratio of 1:1. The oxide electrolytes are ZrO2 and La2O3, with a concentration of 30g / L and a mass ratio of 1:1. The functional polymer additives are polyvinylidene fluoride and polyethylene oxide, with a concentration of 110g / L and a mass ratio of 1:1. The solvents are N,N-dimethylformamide and N-methylpyrrolidone, with a volume ratio of 1:3.

[0215] S2. Prepare electrolyte slurry

[0216] Add a mixture of N,N-dimethylformamide and N-methylpyrrolidone, a mixture of LiCl and LiNO3, a mixture of ZrO2 and La2O3, and a mixture of polyvinylidene fluoride and polyethylene oxide to the reaction container in sequence. During the addition process, the high-speed disperser continues to work and the stirring speed is controlled at 2000 rpm. After the addition is completed, stirring is continued for 1 hour, and then the ultrasonic stirrer is used for 2 hours at 2000 W. Then, the high-speed disperser is used to stir at 2000 rpm for 2 hours. After standing for 4 hours, the above stirring process is repeated once.

[0217] S3. Coating solid electrolyte

[0218] A PE base film was selected with a thickness of 16 μm, a porosity of 50%, a coating speed of 200 mm / s, and a negative pressure of -10 kPa.

[0219] S4, Solidified solid electrolyte

[0220] Initial curing: curing temperature is 60°C and curing time is 1 hour.

[0221] Secondary curing: curing temperature is 60°C, pressure is 0.5MPa, electric field voltage is 100V, electric field angle is 90°, and curing time is 2 hours.

[0222] The solid electrolytes prepared by the methods of the above-mentioned Examples 1 to 10 and Comparative Examples 1 to 4 were respectively prepared into button-type secondary batteries for ion conductivity testing. The solid electrolyte membrane was cut into discs, and after the thickness was tested, it was clamped between two pieces of stainless steel to form a "sandwich" structure, placed in a button-type battery housing, and then injected with a liquid electrolyte of DC:DMC:DEC=1:1:1 / LiPF6, and packaged to obtain a button-type secondary battery. The ionic conductivity of the button-type secondary battery was tested by an electrochemical workstation in an environment of 25°C, and the test frequency was set to 10 -1 ~10 5 Hz, amplitude 10mV. The test results are shown in Table 1 below.

[0223] Table 1 Ionic conductivity test results

[0224] Test samples Ionic conductivity (mS / cm) Example 1 1.212 Example 2 0.853 Example 3 0.664 Example 4 0.573 Example 5 0.784 Example 6 0.559 Example 7 0.674 Example 8 0.877 Example 9 0.855 Example 10 0.631 Comparative Example 1 0.149 Comparative Example 2 0.153 Comparative Example 3 0.248 Comparative Example 4 0.021

[0225] It can be seen from the test data in the table that the ionic conductivity of the solid electrolyte prepared by the method of the present invention is much higher than that of all the comparative examples, which proves that the solid electrolyte prepared by the preparation method of the present application can in situ construct a uniform and dense solid electrolyte film with preferentially guided lithium ion transmission channels through the synergistic effect of electric field, temperature field and pressure field during the solidification process, thereby significantly reducing the lithium ion migration energy barrier and improving the ionic conductivity.

[0226] from Figure 2 , Figure 3 , Figure 4 It can be seen that the solid electrolyte prepared by the preparation method of the present invention can form an efficient transmission channel with the ability of directional lithium ion transport, while the solid electrolytes prepared by the methods of Comparative Example 1 and Comparative Example 4 cannot form a transmission channel with the ability of directional lithium ion transport.

[0227] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that it is still possible to modify the technical solutions described in the aforementioned embodiments, or to replace some or all of the technical features therein by equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

Claims

1. A method for preparing a base film supported high ionic conductivity solid electrolyte, characterized in that: The following steps are involved: Preparation of solid electrolyte precursor: Prepare solid electrolyte precursor using plastic inorganic lithium salt, oxide electrolyte, superionic conductor and functional polymer additive as raw materials; Prepare electrolyte slurry: add solvent, plastic inorganic lithium salt, superionic conductor, oxide electrolyte, and functional polymer additive into the reaction container in sequence, and use a disperser to continuously stir during the addition process; Applying solid electrolyte slurry: applying the solid electrolyte slurry on the base film; Solidified solid electrolyte: includes two solidification stages, in which only the temperature is controlled during the initial solidification, and the temperature field, pressure field and electric field are introduced during the secondary solidification.

2. The method for preparing a base film supported high ionic conductivity solid electrolyte according to claim 1, characterized in that: The plastic inorganic lithium salt includes any one or more combinations of LiCl, LiBr, Li2S, and LiNO3.

3. The method for preparing a base film supported high ionic conductivity solid electrolyte according to claim 1, characterized in that: The oxide electrolyte includes any one of ZrO2 and La2O3 or a combination of two of them.

4. The method for preparing a base film supported high ionic conductivity solid electrolyte according to claim 1, characterized in that: The superionic conductor includes any one of two-dimensional nanomaterials and three-dimensional porous nanomaterials or a combination of the two.

5. The method for preparing a base film supported high ionic conductivity solid electrolyte according to claim 4, characterized in that: The two-dimensional nanomaterial includes any one of graphene, graphene derivatives, boron nitride, transition metal sulfide, carbon nitride, and two-dimensional transition metal carbide.

6. The method for preparing a base film supported high ionic conductivity solid electrolyte according to claim 4, characterized in that: The three-dimensional porous nanomaterials include organic metal frameworks, covalent organic frameworks, hydrogen bond organic frameworks and derivatives thereof.

7. The method for preparing a base film supported high ionic conductivity solid electrolyte according to claim 1, characterized in that: The functional polymer additive includes any one or more combinations of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-chlorotrifluoroethylene copolymer, polyethylene oxide, and polytetrafluoroethylene.

8. The method for preparing a base film supported high ionic conductivity solid electrolyte according to claim 1, characterized in that: The solvent includes any one or more combinations of N,N-dimethylformamide, N-methylpyrrolidone and tetrahydrofuran.

9. The method for preparing a base film supported high ionic conductivity solid electrolyte according to claim 1, characterized in that: During the primary curing process, the curing temperature is 40-85°C; during the secondary curing process, the curing temperature is 40-85°C, the pressure is 0.01-1MPa, the electric field voltage is 50-200V, and the angle between the electric field direction and the horizontal direction is 30-90°.

10. The method for preparing a base film supported high ionic conductivity solid electrolyte according to claim 1, characterized in that: The concentration ratio of plastic inorganic lithium salt, oxide electrolyte, superionic conductor and functional polymer additive is (17.0-60.8): (20-120): (2.4-26): (80-130).

11. The method for preparing a base film supported high ionic conductivity solid electrolyte according to claim 1, characterized in that: When the solid electrolyte slurry is coated on the base film, the coating speed is 50 to 2000 mm / s and the pressure is controlled at -1 to -100 kPa.

12. A base film supported high ionic conductivity solid electrolyte, characterized in that: The preparation method is described in any one of claims 1 to 11.

13. A secondary battery, characterized in that: Comprising the solid electrolyte according to claim 12.

14. A secondary battery according to claim 13, characterized in that: The preparation method of the secondary battery is as follows: a solid electrolyte film is cut into discs, and then clamped between two pieces of stainless steel to form a "sandwich" structure, which is placed in a battery housing, and then a liquid electrolyte is injected and packaged to obtain a secondary battery.